2007
DOI: 10.1128/aem.01551-07
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Iron in Human Serum Resistance of the Clinical and Environmental Vibrio vulnificus Genotypes

Abstract: We recently reported a simple PCR procedure that targets a sequence variation of the virulencecorrelated gene locus vcg. It was found that 90% of all clinical isolates possessed the vcgC sequence variant, while 93% of all environmental isolates possessed the vcgE sequence variant. Here we report that the clinical genotype of Vibrio vulnificus is significantly better able to survive in human serum than is the environmental genotype. The presence of a siderophore-encoding gene, viuB, influenced serum survivabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 19 publications
2
24
1
Order By: Relevance
“…In addition, multiplex polymerase chain reaction (PCR) studies by Panicker et al [28] showed that clinical isolates were more likely to be positive for the siderophore-encoding gene viuB than environmental isolates. Regarding the prevalence of viuB , Bogard et al [29] found that serum survivability of the viuB- positive isolate was greater than that of the viuB -lacking ones. Bacterial genotyping methods focusing on differences between clinical and non-clinical types have been performed for individual or two to four combinations of genes; however, genotypic analysis of a combination of five genes participating in V. vulnificus infection has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, multiplex polymerase chain reaction (PCR) studies by Panicker et al [28] showed that clinical isolates were more likely to be positive for the siderophore-encoding gene viuB than environmental isolates. Regarding the prevalence of viuB , Bogard et al [29] found that serum survivability of the viuB- positive isolate was greater than that of the viuB -lacking ones. Bacterial genotyping methods focusing on differences between clinical and non-clinical types have been performed for individual or two to four combinations of genes; however, genotypic analysis of a combination of five genes participating in V. vulnificus infection has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…V. vulnificus is widely recognized as a human pathogen, although genetic analyses have revealed that strains of this species are not equally pathogenic. Genotyping has revealed differences not only in pathogenic potential but also in the ecological niches in which these strains reside (11,12,53). Genetic dimorphisms among V. vulnificus strains have been documented on a genome-wide scale; thus, it has been proposed that C-and E-genotype strains may reflect distinct ecotypes (10,13).…”
Section: Figmentioning
confidence: 99%
“…The use of multilocus sequence typing and phylogenetic analyses of sequenced genomes has further delineated C and E genotypes into two distinct evolutionary lineages (9,10). Indeed, previous studies have shown that C-and E-genotype strains display different ecologies, in which E-genotype strains seem to have a distinctive advantage in inhabiting oysters, whereas C-genotype strains are more successful in infecting the human host (7,(11)(12)(13). Furthermore, genome comparisons have allowed the identification of several putative virulence factors (such as the genomic XII region) that could potentially aid C-genotype strains in disease progression (10,14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have provided further distinctions between these genotypes. Specifically, we have found that C-genotype strains demonstrate superior survival in human serum relative to E-genotype strains (12)(13)(14), and genome comparisons have allowed the identification of several putative virulence factors that could potentially aid this bacterium in disease progression (15,16).…”
mentioning
confidence: 99%